Health Literacy and Medication Adherence in COPD Patients: When Caregiver Presence Is Not Sufficient. (2nd November 2019) - Muellers, Kimberly A.; Chen, Li; O'Conor, Rachel; Wolf, Michael S.; Federman, Alex D.; Wisnivesky, Juan P.
Abstract: Limited health literacy (HL) is associated with a lower medication adherence in patients with chronic obstructive pulmonary disease (COPD). In this study, we examined the potential mitigating role of caregiver support on the relationship between HL and adherence to COPD medications. We conducted a prospective observational study of adults with COPD and their caregivers. HL was assessed using the Short Test of Functional Health Literacy in Adults (S-TOFHLA) and COPD medication adherence was evaluated with the Medication Adherence Rating Scale (MARS). We also collected caregiver HL data for a subset of participants. We tested whether having a caregiver impacted the relationship between HL and medication adherence using cross-sectional data collected between 2011 and 2015. Our sample included 388 COPD patients and 97 caregivers. COPD patients with low HL had a lower medication adherence (odds ratio [OR]: 0.44, 95% confidence interval [CI]: 0.24–0.81) after adjusting for sociodemographic factors. Caregiver presence was not associated with increased patient medication adherence (OR: 1.28, 95% CI: 0.79–2.08). Among the subset of patients with caregivers, low patient HL remained associated with a lower medication adherence (OR: 0.28, 95% CI: 0.09–0.82) when adjusted for caregiver HL and sociodemographic factors. Low HL is associated with lower COPD medication adherence, and this effect is not mitigated by the presence of a caregiver. These findings suggest a need for effective strategies to manage high-risk COPD patients with low HL, even among those with adequate support from caregivers, and to design interventions for both patients and caregivers with low HL.